Regulation of Placental Calcium Transport and Offspring Bone Health - Goodfellow, Laura; Cooper, Cyrus; Harvey, Nicholas C. (Frontiers in Endocrinology, 2011)
Osteoporosis causes considerable morbidity and mortality in later life, and the risk of the disease is strongly determined by peak bone mass, which is achieved in early adulthood. Poor intrauterine and early childhood growth are associated with reduced peak bone mass, and increased risk of osteoporotic fracture in older age. In this review we describe the regulatory aspects of intrauterine bone development, and then summarise the evidence relating early growth to later fracture risk. Physiological systems include vitamin D, PTH; leptin; GH/ IGF-1; finally the potential role of epigenetic processes in the underlying mechanisms will be explored. Thus factors such as maternal lifestyle, diet, body build, physical activity and vitamin D status in pregnancy all appear to influence offspring bone mineral accrual. These data demonstrate a likely interaction between environmental factors and gene expression, a phenomenon ubiquitous in the natural world (developmental plasticity), as the potential key process. Intervention studies are now required to test the hypotheses generated by these epidemiological and physiological findings, to inform potential novel public health interventions aimed at improving childhood bone health and reducing the burden of osteoporotic fracture in future generations.